The Cosmological Dimension of the Dabus Dance: Purification and Healing Practices: (Dimensi Ruang Kosmos Tarian Dabus: Amalan Penyucian dan Penyembuhan) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2016)
This paper is an attempt to examine the diversity of the dimension of cosmological spaces in the dabus dance performances from the aspect of physical and metaphysical. Qualitative research used by applying ethnographic strategy which focuses on the relationship between behavioural actions and culture. Cosmologically, the dabus dance is seen as a cosmos where the existence of its form is derive from the actions of the performerand all of theatrical elements that formed the dabus performance. The dimension of dabus dance cosmological spaces is analysed physically and metaphysically by looking at the action of the performer and their belief that emphasized the phenomenon of purification and healing practice. Based on these beliefs, offerings are prepared and rituals are done in the dabus performance with the main aim of respecting and asking permission from these spiritual beings to help with the healing process, which in the dabus ritual can be categorized as faith healing, vis-à-vis ritual practices which are related to religious beliefs. The healing came about because of the belief in the intervening powers and abilities of these spiritual/other worldly beings. This belief is exposed through the influence of spirit on taboos that is practice by the performer. The unconscious phenomenon experienced by the dancer during performance is a sign that performers' psyche and action is taken over by the spiritual being. Thus, unconscious situation is about taking over of the body of the performer by the entity beyond physical reality. In relation to that, the focus of this discussion is about the relationship between cosmological spaces and the concept of cleansing and purification as a cause for the dabus dance ritual to happen.Keywords: dabus dance, physical, cosmos, metaphysic, sub-conscious, faith healing